POLG mutations lead to abnormal mitochondrial remodeling during neural differentiation of human pluripotent stem cells via SIRT3/AMPK pathway inhibition. Issue 11 (3rd June 2022) - Chen, Anbin; Kristiansen, Cecilie Katrin; Høyland, Lena Elise; Ziegler, Mathias; Wang, Jian; Sullivan, Gareth John; Li, Xingang; Bindoff, Laurence A.; Liang, Kristina Xiao
ABSTRACT: We showed previously that POLG mutations cause major changes in mitochondrial function, including loss of mitochondrial respiratory chain (MRC) complex I, mitochondrial DNA (mtDNA) depletion and an abnormal NAD + /NADH ratio in both neural stem cells (NSCs) and astrocytes differentiated from induced pluripotent stem cells (iPSCs). In the current study, we looked at mitochondrial remodeling as stem cells transit pluripotency and during differentiation from NSCs to both dopaminergic (DA) neurons and astrocytes comparing the process in POLG-mutated and control stem cells. We saw that mitochondrial membrane potential (MMP), mitochondrial volume, ATP production and reactive oxygen species (ROS) changed in similar ways in POLG and control NSCs, but mtDNA replication, MRC complex I and NAD + metabolism failed to remodel normally. In DA neurons differentiated from NSCs, we saw that POLG mutations caused failure to increase MMP and ATP production and blunted the increase in mtDNA and complex I. Interestingly, mitochondrial remodeling during astrocyte differentiation from NSCs was similar in both POLG-mutated and control NSCs. Further, we showed downregulation of the SIRT3/AMPK pathways in POLG-mutated cells, suggesting that POLG mutations lead to abnormal mitochondrial remodeling in early neural development due to the downregulation of these pathways. uf0001